ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI FINANCIAL SUSTAINABILITY RATIO PADA BANK UMUM SYARIAH DI INDONESIA PERIODE 2010 - 2014 (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2016)
This study aimed to analyze the influence of Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), Return on Equity (ROE), Return on Assets (ROA), Financing Deposit Ratio (FDR), Operating Expenses Operating Income (BOPO) on Financial Sustainability Ratio (FSR) of Islamic Banking in Indonesia. The objects were Sharia Commercial Banks in Indonesia registered in Bank Indonesia / OJK period 2010 Q2 – 2014 Q4. In analyzing data, it used panel data regression analysis with the estimation model Fixed Effect, classic assumption test, and hypothesis testing used Eviews 8.0 program. Results of t test showed that the positive effect of CAR was not significant, NPF has significant negative effect, ROE has not significant negative effect, ROA has significant positive effect, FDR has not significant positive effect, and BOPO has significant negative effect. While the results of F test indicate that all independent variables significantly influence the dependent variable with adjusted R2 of 0.9646.